Prototipe Sistem Pemantauan Suhu dan Kelembapan berbasis Fog Computing pada Kumbung Jamur - Bintang Mada Suharsono; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Currently, internet of things (IoT) based technology has been widely applied to monitor temperature and humidity in mushroom cultivation house. Sensors like the DHT11 are involved to sense temperature and humidity. After the data is obtained, then the data is sent to the base station for temporary storage. The base station then forwards the data to a database located in the cloud so that the data can be stored. Users must be connected to the internet first when they want to access data. Internet connection is a must for internet of things based systems. If the mushroom cultivation house location is in a location or area that does not have an internet connection, then the IoT-based system cannot work. This is a problem for this system. Based on these problems, this research tries to overcome these problems by making a prototype of a temperature and humidity monitoring system based on fog computing on mushroom cultivation house. This prototype is made similar to an IoT-based system, but the data can still be accessed even without an internet connection. This can happen because the database and web server are placed on the fog node (Raspberry pi 3) which is on the local network. The result of this research is that the system can be accessed on a local network without involving an internet connection and runs like a cloud-based system. Also, performance testing shows that 25 to 50 meters is a good distance to transmit data.